2008
DOI: 10.4314/ajhs.v14i3.30867
|View full text |Cite
|
Sign up to set email alerts
|

Baseline CD4 lymphocyte count among HIV patients in Kano, Northern Nigeria

Abstract: SUMMARY HIV causes immunodeficiency by infection, lyses and depletion of CD4 T-lymphocytes;hence CD4 count has become a valuable indicator of immune function in the management of HIV infection. Consequently, we evaluated baseline CD4 counts of 500 HIV seropsitive adults in a government sponsored anti-retroviral treatment (ART) scheme at our centre, for the purpose of monitoring subsequent response to anti-retrovirals.The overwhelming majority (92%) of our patients were within the sexually active, 3rd to 5th de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…The difference is statistically significant (p<0.001). This finding is in keeping with reports of HIV incidence in Nigeria (Nwokedi et al, 2007;Ajayi et al, 2009Ajayi et al, , 2011 and outside the country (UAC., 2003; Kilaru et al, 2004). Persons in the age range 20-50 might be predisposed because they represent the reproductive and productive age group of any society and thus sexually active.…”
Section: Discussionsupporting
confidence: 92%
“…The difference is statistically significant (p<0.001). This finding is in keeping with reports of HIV incidence in Nigeria (Nwokedi et al, 2007;Ajayi et al, 2009Ajayi et al, , 2011 and outside the country (UAC., 2003; Kilaru et al, 2004). Persons in the age range 20-50 might be predisposed because they represent the reproductive and productive age group of any society and thus sexually active.…”
Section: Discussionsupporting
confidence: 92%
“…This was significantly higher when compared to the studies conducted in Nigeria, south eastern United States and Thailand which reported a lower rate of AIDS at the initiation of ART. 15,16 Therefore, in the hospital of this current study, delayed enrollment in ART program could be attributed by several factors such as due to fear of stigma. In Ethiopia, as described by the above authors, only one third of HIV infected persons disclosed their HIV status to their partner further compromising the utilization of the counseling and testing and ART services.…”
Section: Discussionmentioning
confidence: 86%
“…Documented data on lymphocytes, especially CD3 and CD4 T cells of a particular population or region will obviously help in important clinical decisions, especially those that concern HIV/AIDS and tuberculosis. However, no published data are available on CD3 T cells of Nigerians and only little data are available on CD4 T cells in Nigeria; and most of the studies were on immunocompromised populations [21–23]. Besides, the few studies performed in apparently healthy individuals in Nigeria did not exclude subjects that were HBV and HCV positive [8, 24]; and the possibility that this may affect the CD4T cell outcomes cannot be underestimated.…”
Section: Introductionmentioning
confidence: 99%